2011
DOI: 10.14310/horm.2002.1306
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mediated "pseudoacromegaly"

Abstract: AbstrAct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Meanwhile, animal studies have indicated that overexpression of murine Elovl6 gene can cause insulin resistance [25]. Combining all the recent studies, enlargement of finger in macrodactyly can be associated with insulin signaling mechanism considering the role of ELOVL6 gene in de novo lipogenesis and insulin resistance like pseudo-acromegaly [26]. Interestingly, the fat tissue was not distinguishable from normal fat tissue, except for the increased size of fat lobules in our case (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Meanwhile, animal studies have indicated that overexpression of murine Elovl6 gene can cause insulin resistance [25]. Combining all the recent studies, enlargement of finger in macrodactyly can be associated with insulin signaling mechanism considering the role of ELOVL6 gene in de novo lipogenesis and insulin resistance like pseudo-acromegaly [26]. Interestingly, the fat tissue was not distinguishable from normal fat tissue, except for the increased size of fat lobules in our case (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…He also has more severe hyperinsulinaemia and is older than his sisters (Table 1). The low serum IGF‐1 levels in our patients may be due to the negative feedback regulation from very high insulin levels acting on the pituitary and hypothalamic IGF‐1 receptors, which has recently been reported in a case with insulin‐mediated pseudoacromegaly 27 …”
Section: Discussionmentioning
confidence: 55%
“…The low serum IGF-1 levels in our patients may be due to the negative feedback regulation from very high insulin levels acting on the pituitary and hypothalamic IGF-1 receptors, which has recently been reported in a case with insulinmediated pseudoacromegaly. 27 Based on the crystal structure of INSR, the central b-sheet of the leucine-rich repeat 1 (L1) domain is a major contributor to ligand binding. 28 The characteristic feature of this L1 ligand-binding surface is a large hydrophobic patch with a cavity at the centre formed by amino acid residues Q34, L36, L62, F64, F88, F89, V94, F96, R118 and E120.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acromegaloid have increased growth hormone and insulin resistance, which makes them insulin-dependent. Glibenclamide is used to treat diabetes [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%